Notes on Early Land Plants Today. 9. Validation of Riccia gangetica Ahmad - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2012)
Riccia gangetica was described without a Latin description. The species has since been accepted by Indian bryologists and was also accepted by Jovet-Ast (2003) in her revision of Indian Riccia species without it being validated.